(untitled) (Iranian Journal of Kidney Diseases, 2019)
Renovascular hypertension is known to occur due to varied causes. Absence of Renal artery stenosis or changes in renal vascular flow make it tough to establish a diagnosis of renovascular hypertension in the absence of invasive investigations. Segmental renal hypoplasia is not only a rare cause for renin mediated hypertension but also requires expertise and high index of suspicion while evaluating children with hypertension. We describe the classical imaging findings of a child with secondary hypertension which was due to hypoplasia of a renal segment